Hubungan Dukungan Keluarga Terhadap Pengendalian Emosi Remaja - Karmila, Karmila; Razzaq, Abdur; Lubis, Anissa Rachmawati (Journal of Society Counseling, 2024)
This research discusses the relationship between family support and emotional control in adolescents at the Palembang Class 1 Special Development Institution for Children. This study aims to determine the level of emotion and the relationship between family support and emotional control in adolescents at a special development institution for grade 1 children in Palembang. This type of research is correlational for the extent to which variations in one variable are related to other variables. Therefore, this research uses a quantitative approach. The results of the research show: First, the results of calculating the mean descriptive data to see the emotional level of teenagers with data obtained in the high category were 23 people with a percentage of 92%, in the medium category there were 1 person with a percentage of 4% and in the low category there were 16 people with a percentage of 4%. The results can be concluded that the emotional level in teenagers is still relatively high and difficult to control while at the Palembang Class I Special Development Institute for Children. Second, the SPSS output results for the linearity test prove that the correlation test value for the Family Support variable (X) for teenagers is 0.370 with a positive direction. Meanwhile, the Emotional Approach variable (Y) is 0.690. To see the relationship between the two sides of the variable, the value of sig deviation from linearity = 0.692 > 0.05, it can be stated that there is a relationship between the two variables It can be concluded that there is a very strong relationship between family social support and emotional control in adolescents at the Palembang Class I Special Development Institution for Children.